Dispositional forgiveness approach through an ecological systems theory: A systematic review - Sari, Kartika; Yusuf, Rusli; Ishak; Mawarpury, Marty (Insight: Jurnal Ilmiah Psikologi, 2025)
Research on dispositional forgiveness has primarily concentrated on the intraindividual level. The aim of this study is to analyze dispositional forgiveness using ecological systems theory, with a systematic review and thematic analysis technique. A literature search was performed from 2018 to 2025 in a range of electronic databases: Scopus, PubMed, Google Scholar, and Science Direct. Of 26,550 results from the searches, 15 articles fulfilled the inclusion criteria and were chosen for analysis. Thematic analysis indicates that dispositional forgiveness research is primarily undertaken within the microsystem, including personality, well-being, resilience, self-efficacy, emotional intelligence, self-acceptance, attachment and anxiety. Studies on macrosystem dimensions, involving cultural and historical variables that determine individual forgiveness, are limited. Researchers can use the findings of this study as a reference to perform exploratory research on cultural values and historical circumstances that influence forgiveness attributes. Empirical research is also needed, particularly on children. Keywords: dispositional forgiveness; ecological systems theory; microsystem; systematic review